Inter-robot communication and its implementation in a PDA-based teleoperation of multiple mobile robots - Djong, Januardy (2010)
A motivation for investigating multi-robot communication is that it enables teams of robots to maximize their utility. The coordination of a team of robots would be impossible without communications. Hence, communication is one of the key infrastructures to have a robot team. Moreover, advancement of wireless technology has enabled development of telerobotics and wireless communication system. Integrating these two technologies, it is possible to achieve a cooperative robot team teleoperated by human supervisor to accomplish a human – robot team collaboration in performing numerous tasks. Previous development has successfully deployed multiple mobile robots teleoperated by a PDA. The system, however, lacks the communication feature to enable robot cooperation. Two problems are addressed during development of communication feature. The first is communication protocol, which consists of transport and message content layer. The transport layers provide a channel between sender and receiver over which information are exchanged. The content layers build the format of the information being communicated. The second problem is the communication architecture. Centralized architecture whereby all communication occur flow through a central server agent is being chosen. The centralized architecture is preferred in this stage of research since supervision by human operator is considerably easier than an opposite peer-to-peer configuration where communication does not flow through central agent. A preliminary study to observe the performance of communication and broadcasting with various types of data was successfully conducted.